"People Who Act like Dogs": Adultery and Deviance in a Melanesian Community - Counts, Dorothy Ayers; Counts, David R. (Anthropologica, 2022)
Sociological studies of deviance, especially labelling theory, are concerned with the labels used by society to identify deviants and with the long term effect of labelling for the people who are thus categorized (see Becker 1966; Lemert 1967). These studies have focussed primarily on large-scale societies, with little attention being paid by anthropologists to labelling of deviance in small-scale communities (but see Edgerton 1966, 1976). This essay is a study of the way in which the people of a small-scale, horticultural community in Papua New Guinea identify and respond to people who engage in deviant acts. We focus on the act of adultery and the range of responses to it, and we argue that the analysis of deviance in small-scale societies must discriminate between behaviour that merely breaks the rules and behaviour that causes conflict which may not readily be resolved and, consequently, may lead to the permanent disruption of social relationships.